Sociolinguistics in the digital era: Minang language as cultural identity - Ahmadi, Yondri; Yasmadi, Yasmadi; Fitri, Titi (Universitas Muhammadiyah Purwokerto, 2024)
Indonesia is renowned for its abundant ethnic and cultural diversity, where each community upholds its unique language and traditions. This study aims to delve into the sociolinguistic dynamics in the digital age, focusing particularly on the Minang language as a cultural emblem. Employing a descriptive qualitative approach, the research meticulously delineates the distinctive features of the Minang language as an inseparable facet of cultural heritage. Methodologically, a literature review is employed to gather data from diverse secondary sources such as books, literature, and relevant media, subsequently subjecting them to content analysis techniques to decipher the meanings embedded in expert expressions and perspectives within the realm of scholarly discourse. The findings underscore the intricate impact of the digital era on the Minangkabau language and culture, encompassing the pervasive influence of technology and mass media on its usage, preservation, and evolution within society. The dynamics of urbanization and population mobility also wield significant influence, presenting challenges in preserving traditional cultural practices amidst the currents of modern urban life. To safeguard the rich tapestry of Minangkabau culture, concerted efforts are imperative, including educational initiatives rooted in local cultural values, leveraging digital technologies for cultural documentation and advocacy, alongside governmental support and active engagement from local communities. Collaborative endeavors across sectors are envisaged as pivotal in safeguarding the Minangkabau language as a cherished symbol of cultural identity, resonating not just locally but also on the global stage increasingly interconnected in the digital era.